Evaluation of Internal Control on the Siakad Application at Politeknik Kesehatan Bhakti Setya Indonesia Using Cobit 2019 - Adi Cahyo Kuswijayanto; Suhirman; Joko Sutopo; Muhammad Senoaji Wibowo (Jurnal E-Komtek, 2026)
The digitalization of higher education has made Academic Information Systems (SIAKAD) essential assets requiring effective IT internal controls. This study evaluates the capability level of internal controls in the SIAKAD application at Poltekkes Bhakti Setya Indonesia (BSI) using the COBIT 2019 framework and identifies improvement opportunities. Data were collected through in-depth interviews with six key respondents, including IT management, SIAKAD operators, and the Head of Academic Affairs, supported by institutional documents. The assessment focused on five COBIT 2019 processes: APO12, DSS01, DSS05, BAI10, and MEA02. The results indicate that most processes remain at Capability Level 1 (Performed Process), while DSS01 achieved Level 2 (Managed Process). The largest capability gap was identified in MEA02, which remains at Level 0 (Incomplete Process), whereas APO12, DSS05, and BAI10 each showed a gap of two levels. These findings provide practical recommendations to strengthen IT governance and achieve Capability Level 3 (Established Process) through standardized procedures and continuous internal monitoring.